2004
DOI: 10.1167/iovs.04-0091
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Drug Release from an Ocular Implant: An Evaluation Using Dynamic Three-Dimensional Magnetic Resonance Imaging

Abstract: In vivo, episcleral implants at the equator of the eye did not deliver a significant amount of Gd-DTPA into the vitreous, and no compound was identified in the posterior segment. A 30-fold increase in vitreous Gd-DTPA concentration occurred in the enucleated eyes, suggesting that there are significant barriers to the movement of drugs from the episcleral space into the vitreous in vivo. Dynamic three-dimensional MRI using Gd-DTPA, and possibly other contrast agents, may be useful in understanding the spatial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 38 publications
2
80
1
Order By: Relevance
“…Dynamic barriers are active in vivo but cease postmortem, while static barriers are always present. A comparison of scans acquired in vivo and postmortem revealed increased penetration of a magnetic resonance imaging tracer released from a polymeric episcleral implant into the anterior chamber and vitreous postmortem but not in vivo [122] . Similar results were obtained after subconjunctival injection of manganese ions [123] .…”
Section: Discussionmentioning
confidence: 95%
“…Dynamic barriers are active in vivo but cease postmortem, while static barriers are always present. A comparison of scans acquired in vivo and postmortem revealed increased penetration of a magnetic resonance imaging tracer released from a polymeric episcleral implant into the anterior chamber and vitreous postmortem but not in vivo [122] . Similar results were obtained after subconjunctival injection of manganese ions [123] .…”
Section: Discussionmentioning
confidence: 95%
“…5). Kim et al (2004) reported that transscleral delivery of gadolinium-diethylenetriaminepentaacetic acid to the vitreous in rabbits was approximately 30-fold higher after euthanasia because of the impairment of dynamic barriers, which include blood and lymphatic clearance pathways. These authors also showed that under in vivo conditions, the elimination rate constant from the subconjunctival space into episcleral veins and conjunctival lymphatics was 3 log units higher than the transport rate constant into the vitreous.…”
Section: Thakur Et Almentioning
confidence: 99%
“…Particularly, blood vasculature clearance is a major barrier in transscleral transport (Li et al, 2004b). Conjunctival lymphatic clearance and other factors (Kim et al, 2004) also contribute to the transscleral barrier. The similarity of the results of transscleral iontophoresis in vivo and subconjunctival injection postmortem suggests that the applied electric field can potentially drive the permeants across the barrier due to clearance such as the blood vasculature barrier to enhance drug delivery.…”
Section: Transscleral Iontophoresismentioning
confidence: 99%
“…Studies employing MRI to follow ocular drug delivery in rabbits have been reported (Li et al, 2004a,b;Kim et al, 2004). An aim of the earlier experiments was to assess MRI as a technique to study ocular delivery and pharmacokinetics in an animal model (Li et al, 2004a,b).…”
Section: Introductionmentioning
confidence: 99%